Manufacturing the activated carbon catalyst of impregnated palm core shells for biodiesel production - Rifki, Ahmad; Zamhari, Mustain; Purnamasari, Indah (Konversi, 2024)
This research aims to produce activated carbon-based heterogeneous catalyst derived from palm kernel shells impregnated with a KOH solution and to determine the effects of the concentration of the KOH solution and the time period during impregnation. The variables observed included KOH concentration and impregnation time. The impregnation process used KOH solution with the solution concentrations of 1N, 2N, 3N, 4N and 5N with impregnation process within 18 hours, 21 hours and 24 hours. AAS, FTIR and SEM were analyzed after impregnation with different concentrations and times. The results of the analysis of potassium metal showed the highest absorption occurred at a concentration of 5N within 21 hours at 25.4570%. The application of the activated carbon catalyst from palm kernel shells was conducted in making biodiesel. The process of making biodiesel was carried out with a reaction time of 120 minutes at a temperature of 60℃ with a molar ratio of 1: 12 using a catalyst of 2% (% w/w). Biodiesel yield testing referred to SNI 04-7182-2015. The analysis results obtained showed 879 kg/m3 density, 6.1 cst viscosity, 0.5 acid number, and 174℃ flash point.